2011
DOI: 10.4046/trd.2011.71.5.355
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Diagnosis of Pleural Metastasis of Renal Cell Carcinoma Using Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration

Abstract: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a useful, safe diagnostic modality for evaluating mediastinal and hilar lymphadenopathy. We report a 51-year-old male who presented with a left renal mass and multiple pleural masses without lung parenchymal lesions. The pleural masses were thought to be metastatic tumors or malignant mesothelioma. The patient underwent two percutaneous needle biopsies of the pleural mass, but the specimens were insufficient for a histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Our review of the literature revealed 13 case reports with malignant pleural effusion as the diagnostic presentation of RCC -to the best of our knowledge, making it an extremely rare phenomenon. The cases are listed in Table 1 [2,[6][7][8][9][10][11][12][13][14][15][16]. The primary presenting symptom was dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature revealed 13 case reports with malignant pleural effusion as the diagnostic presentation of RCC -to the best of our knowledge, making it an extremely rare phenomenon. The cases are listed in Table 1 [2,[6][7][8][9][10][11][12][13][14][15][16]. The primary presenting symptom was dyspnea.…”
Section: Discussionmentioning
confidence: 99%